2010
DOI: 10.1074/jbc.m109.083899
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Pathways That Control Farnesoid X Receptor-mediated Hypocholesterolemia

Abstract: Farnesoid X receptor (FXR) plays important regulatory roles in bile acid, lipoprotein, and glucose homeostasis. Here, we have utilized Fxr ؊/؊ mice and mice deficient in scavenger receptor class B type I (SR-BI), together with an FXR-specific agonist and adenovirus expressing hepatocyte nuclear factor 4␣ or constitutively active FXR, to identify the mechanisms by which activation of FXR results in hypocholesterolemia. We identify a novel pathway linking FXR to changes in hepatic p-JNK, hepatocyte nuclear facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 52 publications
6
95
0
Order By: Relevance
“…It is therefore most conceivable that reduction of plasma cholesterol upon PX treatment in mice that do express hepatic FXR is due to suppressed transcription of apolipoprotein A-I 36 and enhanced expression of scavenger receptor class B-I (SCARB1/SR-BI) upon FXR activation, as reported previously by others. 37 In keeping with this hypothesis, we found upregulation of hepatic SR-BI mRNA as well as protein (data not shown). Thus, de novo cholesterol synthesis by the liver, as supported by a profound upregulation of Hmcgr expression and direct quantification of cholesterol synthesis using mass isotopomer distribution analysis, apparently compensates for the increased loss of cholesterol by M A N U S C R I P T…”
Section: Discussionsupporting
confidence: 74%
“…It is therefore most conceivable that reduction of plasma cholesterol upon PX treatment in mice that do express hepatic FXR is due to suppressed transcription of apolipoprotein A-I 36 and enhanced expression of scavenger receptor class B-I (SCARB1/SR-BI) upon FXR activation, as reported previously by others. 37 In keeping with this hypothesis, we found upregulation of hepatic SR-BI mRNA as well as protein (data not shown). Thus, de novo cholesterol synthesis by the liver, as supported by a profound upregulation of Hmcgr expression and direct quantification of cholesterol synthesis using mass isotopomer distribution analysis, apparently compensates for the increased loss of cholesterol by M A N U S C R I P T…”
Section: Discussionsupporting
confidence: 74%
“…3B, C). Increased expression of HNF4 by FXR agonist, GW4064, was reported as a causal factor for FXR-mediated elevation of SR-BI expression in mice (35). However, in our study, HNF4 protein levels were unchanged in these samples, which were in line with the negative results of qRT-PCR.…”
Section: Oca Treatment Did Not Affect Serum Cholesterol and Hepatic Ssupporting
confidence: 55%
“…One study reported that FXR activation by synthetic agonist GW4064 increased transcription factor HNF4 protein levels that led to the transcriptional activation of SR-BI gene through HNF4 binding sequences embedded in the promoter region and intronic sequences of murine SR-BI gene (35). Another study identified multiple functional FXR binding sites (IR1) in the first intron of the murine SR-BI gene (47).…”
Section: Lxr Activation Alone Did Not Induce Hepatic Expression Of Srmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatic LDL receptor (LDLR) expression is not different, but the production of TG-rich, apoB-containing lipoproteins as well as intestinal cholesterol absorption are increased, probably causing the elevated non-HDL-C levels upon FXR defi ciency ( 27 ). In the same line, FXR activation in mice with a synthetic FXR agonist reduces intestinal cholesterol absorption by 50% ( 30 ). The authors propose a reduction in BA pool size and hydrophobicity index (due to an increased tauro-␤ -MCA/TCA ratio) upon FXR activation ( 31 ) as underlying mechanism, as a reduced BA pool hydrophobicity has been associated with a decrease in cholesterol absorption ( 32 ).…”
Section: Bile Acid Metabolismmentioning
confidence: 52%